The Mechanism Underlying the Regulation of Long Non-coding RNA MEG3 in Cerebral Ischemic Stroke - Zhao, Yanfang; Liu, Yingying; Zhang, Qili; Liu, Hongliang; Xu, Jianing (Cellular and molecular neurobiology, 2023)
Cerebral ischemic stroke is one of the leading causes of morbidity and mortality worldwide, and rapidly increasing annually with no more effective therapeutic measures. Thus, the novel diagnostic and prognostic biomarkers are urgent to be identified for prevention and therapy of ischemic stroke. Recently, long noncoding RNAs (lncRNAs), a major family of noncoding RNAs with more than 200 nucleotides, have been considered as new targets for modulating pathological process of ischemic stroke. In this review, we summarized that the lncRNA-maternally expressed gene 3 (MEG3) played a critical role in promotion of neuronal cell death and inhibition of angiogenesis in response to hypoxia or ischemia condition, and further described the challenge of overcrossing blood–brain barrier (BBB) and determination of optimal carrier for delivering lncRNA’ drugs into the specific brain regions. In brief, MEG3 will be a potential diagnostic biomarker and drug target in treatment and therapy of ischemic stroke in the future.